A Morphological Analysis of Slang Words Used in Tiktok Content - Apriliana, Apriliana; Rugaiyah, Rugaiyah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
TikTok is a social media platform popular among the younger generation and a platform for the development of linguistic innovation, particularly in the form of digital slang. This study aims to identify and categorize slang types based on the morphological processes that appear in TikTok video content, captions, comments, and text. The method used is descriptive qualitative, with online data collection from popular content published between 2023 and 2025. The analysis was based on Yule's (2022) word formation theory. A total of 50 slang entries were reviewed and classified into five types of morphological processes: acronym, clipping, derivation, blending, and coinage. The results showed that the most dominant processes were acronym, clipping, derivation, and blending. Coinage was not found in the data. These findings demonstrate the linguistic creativity of TikTok users in developing communication strategies that simultaneously construct social identities in the digital space. TikTok slang not only functions as a form of language but also reflects cultural practices and group communication patterns in the digital era.